Public health experiences from interwar Croatia (Yugoslavia) and making western medicine in the 1930s China - Dugac, Željko (Array, 2018)
To gain control and domination over a particular territory, medicine was often used as a tool for promoting different interests. Using the activities of the League of Nations Health Organization and the Rockefeller Foundation on the territory of China in 1930s, this paper analyses the interconnection of the international and local factors in the transformation of the traditional Chinese milieu to suit the new and trendy public health projects. These activities were conducted not only to improve the public health conditions in the country, but also to introduce the Chinese public health to the processes of internationalization and standardization to the west oriented type of medicine and medical education. Initiated processes necessarily interfered with the political influences, economical interests and cultural environment as well as with military actions in this very turbulent time of Chinese history. Public health activities were carried out by the group of international experts. Among them the main position took two Croatian physicians: Andrija Štampar (one of the founders of the World Health Organisation later) and Berislav Borčić (a director of the School of Public Health in Zagreb). On the basis of correspondence between these two physicians, as well as the travel diary of Andrija Štampar, this essay presents some less known details about the situation in China and the interlacing between politics and medicine.